Pareto Improvement through Unilateral Matching of Public Good Contributions: The Role of Commitment - Wolfgang Buchholz; Richard Cornes; Wolfgang Peters; Dirk Rübbelke (Center for Economic Studies and ifo Institute (CESifo), 2014)
When providing public goods through voluntary contributions, a donor may introduce unilateral matching in order to reduce underprovision of the public good and thus inefficiency. By itself, however, matching benefits the donor but harms the recipient. We apply Cornes and Hartley's aggregative game approach to provide a novel graphical explanation of this transfer paradox, and also show how it may be avoided by introducing a commitment device.
Keywords: H23; H41; 330; voluntary public good provision; matching; commitment